Tracing metals from source to sink in Irish-type Zn-Pb(-Ba-Ag) deposits - Wilkinson,JJ (IAEG, 2023)
The Irish Midlands Zn-Pb(-Ba-Ag) Orefield represents one of the best studied palaeo-hydrothermalsystems worldwide. Despite this, the detailed origins of ore and trace metals and the controls of their variability indeposits across the Orefield, have not been considered in detail. In this contribution, I have used diverse data sourcesin an attempt to track the metals from their source and assess how they were fractionated at various stages alongthe reconstructed flow path. This includes: (1) circulation of fluids to depths of up to ~7 km in the Lower Palaeozoicwedge of arc-derived detritus that underlies the Orefield and through a primary ‘reaction zone’; (2) fluid transitwithin the wedge and then up through the redox boundary represented by the Old Red Sandstone; and (3) fluidingress into the receptive Lower Carboniferous host rocks in the ore deposits themselves, initially through focusedfeeder pipes and then spreading out upwards and especially laterally into the surrounding carbonate units. Theresults show that the Lower Palaeozoic package was a particularly fertile source from which metals were easilyextracted and that this exerted a primary control on metal tenor in the overlying deposits. However, additionalfractionation steps, including loss to and extraction of metals from, the Old Red Sandstone, and sequential deposition of metals during cooling, neutralisation and fluid mixing were also important. The presence beneath the IrishMidlands Basin of a weakly metamorphosed rock package formed from arc-derived detritus is considered to be acritical component of the mineral system.